(untitled) (Cadernos de Sociomuseologia, 2022)
This article addresses part of the political, professional and spiritual trajectory of Yalorixa (a Candomble female priestess), Master in Education, specialist in Youth and Adult Education, Black Movement militant, Maria Conceição da Silva, with the objective, through this narrative, of registering and preserving the history of popular movements, black culture and Youth and Adult Education in Olinda, a city in the state of Pernambuco, Brazil. The life story, the basis of this article, was narrated in the virtual lecture "Memories of Blackness: the popular movement in the outskirts of Olinda as the Heritage of Youth and Adult Education", promoted and recorded on video, on July 9, 2020, by the Collective of researchers of the Masters and PhD course in Museology from the Lusófona University of Humanity and Technologies (ULHT), called Sociomuseology+Paulo Freire. Keywords: Yalorixá; Popular movements; Black culture; Olinda, Eduacation